2022
DOI: 10.1136/bmjopen-2022-062240
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in detecting and managing mild cognitive impairment in primary care: a focus group study in Shanghai, China

Abstract: IntroductionDetection of mild cognitive impairment (MCI) is essential in slowing progression to dementia. Primary care plays a vital role in detecting and managing MCI. The chronic care model (CCM) provides effective methods to manage chronic diseases.ObjectiveThis study aimed to explore how MCI services are delivered in primary care in China.MethodsFocus group interviews were conducted face to face among MCI stakeholders from six community health centres (CHCs) involved in the ‘friendly community programme’ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We found that 87.5% of participants had poor knowledge, and with the rise in the prevalence of dementia and Alzheimer's disease among the continuously aging population, a focus is being placed on early detection and treatment. Difficulties diagnosing and managing mild cognitive impairment, which is usually the first presentation of dementia, are attributed to a triad of hesitant patients, unprepared healthcare providers, and environments of misconceptions and false beliefs [ 16 ]. However, Alzheimer's remains less known in the community than other chronic diseases among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 87.5% of participants had poor knowledge, and with the rise in the prevalence of dementia and Alzheimer's disease among the continuously aging population, a focus is being placed on early detection and treatment. Difficulties diagnosing and managing mild cognitive impairment, which is usually the first presentation of dementia, are attributed to a triad of hesitant patients, unprepared healthcare providers, and environments of misconceptions and false beliefs [ 16 ]. However, Alzheimer's remains less known in the community than other chronic diseases among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has some implications for the formulation of primary healthcare policy. Current primary health care still faces serious challenges in detection and management of cognitive impairment (Lu et al, 2022). The cognitive impairment of nursing home residents over 80 is a problem that cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…That requires healthcare providers to pay more attention to the health of nursing home residents, especially cardiopulmonary function and HRQOL. Thus, there is an urgent need to provide a range of support to facilitate healthcare providers to offer accessible, affordable and appropriate cognitive impairment-related primary healthcare services for nursing home residents, such as clinical practice guidelines, policy and financial support, and information infrastructures (Lu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cognition is multifaceted and MCI can affect many different cognitive domains [24], assessing cognitive function in all domains with a short test is not feasible; thus, instruments must strike a proper balance between the duration and depth of testing to maximize their utility [9]. A consensus of clinical and research experts focused on MCI and AD indicated that a useful cognitive tool should encompass multiple cognitive domains and, at a minimum, assess memory and executive function [9].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%